Survival of Bradyrhizobium sp. under different growth temperatures - Figueiredo, Márcia do Vale Barreto; Balatti, Antônio Pedro; França, Francisca Pessôa de; Burity, Hélio Almeida (Pesquisa Agropecuaria Brasileira, 1995)
The survival of Bradyrhizobium sp. under different growth temperatures, as well as the effectiveness of that strain in relationship to the longevity of the inoculant were evaluated through the study of the behaviour of the strain Bradyrhizobiun by observing the cellular growth and the pH evolution. The bacterial suspension was multiplied in fermentator at the temperatures of 28 oC and 37 oC in YEMA medium. The substrates were: diatomite, diatomite + soil 20% and peat. The evaluation of viable cells was carried out by the methods of plate dilution and plant infection, with sampling at the intervals of 0, 15, 30, 60, 120 e 240 days of storage at a temperature of 5 oC. The strain grown under 28 oC showed a population of 105 cells/m1 after 72 hours of process, and remained constant up to 240 days in all of the substrates. Under the temperature of 37 oC, within 72 hours of process the population was 105-106 cells/ml. For the peat, excellent survival was observed even at this low initial concentration, detected in less than 30 days of storage. Concentrations of 109 cells/g of peat remained constant up to 240 days. In the other vehicles the values reached 107-108 cells/g.